Analysis of the antigen specificity of the human serum immunoglobulin G immune response to complicated gonococcal infection. - Hook, E W (1984)
The antigen-specific basis of human serum immunoglobulin G antibody response to complicated gonococcal infection was studied in 13 patients by using the Western blot technique for transfer of proteins from sodium dodecyl sulfate-polyacrylamide gels to nitrocellulose paper. Of 13 patients (8 with disseminated gonococcal infection, 4 with pelvic inflammatory disease, 1 with gonococcal epididymitis), 12 reacted with protein I antigens and 9 with lipopolysaccharide (LPS). Sera from eight patients reacted with both protein I and LPS, whereas sera from four reacted only with protein I, and one sera reacted with LPS alone. One serum with antibody to both protein I and LPS by Western blot analysis was tested for bactericidal activity before and after adsorption of antibody to LPS. Removal of antibody to LPS reduced the bactericidal titer of this serum from 1:100 to 1:50, indicating that antibody to both antigens may be bactericidal for Neisseria gonorrhoeae.